AcetylacetonateBODIPY‐Biscyclometalated Iridium(III) Complexes: Effective Strategy towards Smarter Fluorescent Photosensitizer Agents1. Issue 42 (6th July 2017) - Palao, Eduardo; Sola‐Llano, Rebeca; Tabero, Andrea; Manzano, Hegoi; Agarrabeitia, Antonia R.; Villanueva, Angeles; López‐Arbeloa, Iñigo; Martínez‐Martínez, Virginia; Ortiz, Maria J.
Abstract: Biscyclometalated Ir III complexes involving boron‐dipyrromethene (BODIPY)‐based ancillary ligands, where the BODIPY unit is grafted to different chelating cores (acetylacetonate forIr‐1 andIr‐2, and bipyridine forIr‐3 ) by the BODIPY meso position, have been synthesized and characterized. Complexes with the BODIPY moiety directly grafted to acetylacetonate (Ir‐1 andIr‐2 ) exhibit higher absorption coefficients ( ϵ ≈4.46×10 4  m −1  cm −1 and 3.38×10 4  m −1  cm −1 at 517 nm and 594 nm, respectively), higher moderate fluorescence emission ( φ fl ≈0.08 and 0.22 at 528 nm and 652 nm, respectively) and, in particular, more efficient singlet oxygen generation upon visible‐light irradiation ( φ Δ ≈0.86 and 0.59, respectively) than that exhibited byIr‐3 ( φ Δ ≈0.51, but only under UV light). Phosphorescence emission, nanosecond time‐resolved transient absorption, and DFT calculations suggest that BODIPY‐localized long‐lived 3 IL states are populated forIr‐1 andIr‐2 . In vitro photodynamic therapy (PDT) activity studied forIr‐1 andIr‐2 in HeLa cells shows that such complexes are efficiently internalized into the cells, exhibiting low dark‐ and high photocytoxicity, even at significantly low complex concentration, making them potentially suitable as theranostic agents. Abstract : Kill and cure : New boron‐dipyrromethene (BODIPY)–iridium(III) complexes, synthesized by a straightforward synthetic approach, exhibit efficient singlet oxygen generation, low dark and high photocytoxicity under visible radiation even at low photosensitizer concentrations.